PENGARUH SUMBER DAYA MANUSIA DAN PENGENDALIAN INTERNAL TERHADAP KECURANGAN AKUNTANSI STUDI PADA PT PEGADAIAN (PERSERO) DI KOTA BANDA ACEH - Harum Nazra Fazini; Suparno Suparno (Jurnal Ilmiah Mahasiswa Ekonomi Akuntansi, 2018)
The purpose of this study was to test the effect of the human resource and internal control over accounting fraud. The study population was the branch manager and employees of PT Pegadaian (Persero) in Banda Aceh as many as 24 respondents. Analysis of the data used is multiple linear regression using SPSS. The results of this study found that human resources and internal controls significant effect either together or partially. The results also showed that the value of R Square of amounting to 0.215, can be interpreted by 21.5 percent of the variation that occurs in the variable accounting fraud at PT Pegadaian (Persero) in Banda Aceh can be explained and influenced by independent variables (human resources and internal control) at PT Pegadaian (Persero) in Banda Aceh. The remaining 78.5 percent is explained by other variables not included in this study.